Upaya Menanamkan Kesadaran Perilaku Hidup Bersih dan Sehat (PHBS) Sejak Dini pada Siswa BTQ di Desa Sidodadi Ramunia Kecamatan Beringin - Tukiman, Tukiman; Syarifah, Syarifah; Ashar, Taufik; Nabila, Kharien Nazwa; Andini, Windi; Lingga, Nabila Rizqi (Universitas Islam Negeri Sumatera Utara, 2024)
Bustan Tsamrotul Qolbis (BTQ) School is located in Sidodadi Ramunia Village, Beringin District, Deli Serdang Regency. BTQ is an Integrated Islamic School that upholds Islamic values, including cleanliness. However, based on the results of the observations made, many students still do not understand the concept of PHBS and do not care about the cleanliness of their classrooms. Thus, service regarding PHBS was carried out for BTQ students. The method of approach carried out in conducting community service is interactive lectures and discussions with the school community, such as teachers, students, and canteen managers at BTQ schools. The activity began by filling out the participant attendance list, distributing pre-tests, delivering materials, playing videos and discussion sessions, distributing post-tests, giving a gallon of taps and stacking shelves, as well as group photos and healthy snacks. The results of statistical analysis of measurements showed that the average pre-test score of a total of 40 participants was 14.53 with a standard deviation value of 2,944. Meanwhile, the average score of the post-test is 17.40 with a standard deviation of 2.134. Furthermore, the results of the Paired Sample t-test obtained a p-value of <0.001, then H0 was rejected. This means that there is an influence between the implementation of the training and the level of knowledge of students. Thus, it is hoped that community service participants can apply PHBS in their daily lives and can maintain the handwashing facilities that have been provided by the service team.